Environmental and social disclosures: Link with corporate financial performance. Issue 1 (March 2016) - Qiu, Yan; Shaukat, Amama; Tharyan, Rajesh
Abstract: Environmental and social disclosures entail costs, yet increasingly, large listed firms are making higher and better quality disclosures. In this paper we examine the link between a firm's environmental and social disclosures and its profitability and market value. We find that past profitability drives current social disclosures. However, consistent with the existing evidence, we do not find any relation between environmental disclosures and profitability. Further, while prior literature has largely focussed on environmental disclosure, we find that it is the social disclosures that matter to investors. We find that firms that make higher social disclosures have higher market values. Further analysis reveals that this link is driven by higher expected growth rates in the cash flows of such companies. Overall our findings are consistent with the resource based view of the firm and the voluntary disclosure theory, suggesting that firms with greater economic resources make more extensive disclosures which yield net positive economic benefits.